CONSTRUCTION OF JOKES AND GAMES AS A TOOL OF EDUCATIONAL DEVELOPMENT AGENT OF CHILDREN WITH LEARNING DIFFICULTIES SCHOOL (Fiep Bulletin - online, 2013)
It is known that the game and play are considered facilitating factors for the acquisition and development of social, cognitive and language, among other things human. Based on this assumption, the school teacher is the primary mediator of cultural objects should use more of the games as teaching resources mediators for the development of students. Are developed Ludo pedagogical work with children with learning difficulties at school, from individual and collective consultations, considering the psychology of the game, according to cultural-historical theory. Visa is possible to overcome learning difficulties and construction of the development of individuals, through the educational work of building games. The activities are carried out by members of GEIPEE (Study Group, Intervention and Research in Special Education and Elementary) on the premises of Laboratory Activities Ludo-Recreational (LAR) of FCT / UNESP-Presidente Prudente and results has enabled better learning for children who are learning difficulties.
Keywords: Construction Games; Learning Disabilities; Labour education.